Carbon stock, methanogenesis and methanotrophy in a fluviovolcanic fan from the Central Cordillera based on biomarkers (2017)
Carbon in the Earth is a function of three reservoirs: the oceans, the atmosphere and terrestrial systems. Carbon stored in soils is much higher than the carbon contained in the aboveground biomass and therefore reliable estimates are crucial for a comprehensive understanding of the global carbon cycle. In the tropics, major sinks of organic carbon in soils are wetlands (including mangroves) and Paramos where accumulation of organic matter is maximum due to permanent waterlogged conditions that cause anoxia. Here we analyze another sink of organic carbon that is soils that is not usually taken into account for the regional/global estimates. Mountain flanks with active volcanic activity provide an ideal situation for accumulation and preservation of organic carbon due to the ashfalls and mass flows combined with river flows that accumulate and preserve big amounts of plant remains under anoxia. Under anoxic conditions, methanogenesis becomes the primary route of carbon degradation by Archaea/Bacteria. This process liberates important methane quantities to the atmosphere that are essential to take into regional and global quantifications. In order to estimate methanogenesis and methanothrophy rates in different deposit horizons, archaeal core membrane lipids glycerol bidiphytanil glycerol tetraethers (GDGTs) were studied. Besides, 3-D modeling based on georadar meassurements and the careful description of the outcrop, permitted to estimate the deposit volume and the organic carbon amount contained there. Thus, our results show that those soils are important organic carbon sinks comparable to Paramos and wetlands in the tropics. Moreover, these sinks may turn into organic carbon, methane and carbon dioxide sources if these soil deposits are exposed to oxic conditions, strongly contributing to global warming